QUANTIFICATION OF SODIUM DEOXYCHOLATE IN PROTEOMICS SAMPLE PREPARATION USING METHYLENE BLUE - Makhsatova, S.; Kulyyassov, A. (Eurasian Journal of Applied Biotechnology, 2023)
Anionic detergents like SDC are commonly used in biochemical and molecular biology research for solubilizing and separating proteins and nucleic acids. The detection method using methylene blue (MB) can be employed to determine the concentration of anionic detergents in these experimental preparations. The quantification protocol for surface active substances was optimized, with the consideration of factors such as pH, salts and the spectrophotometer wavelength. Several extraction methods were employed to remove the detergent from the sample, namely, ethyl acetate extraction, mineral oil and acid precipitation. All of the methods have about the same efficiency. The MB method was used as a standard technique for the precise quantification of detergent amounts which allowed as achieving an approximate concentration range between the lower limit of ca. 0.02% and 0.1% of the upper limit. Consequently, we weren’t able to detect the concentration of the detergent lower than 0.02%. In the presence of anionic detergents, the electrostatic interaction between positively charged MB and the anions forms a complex that can be extracted into chloroform, allowing for quantification. Without the formation of this complex, water-soluble MB remains immiscible in chloroform.